Factors influencing the occurrence and vulnerability of the Travancore tortoise Indotestudo travancorica in protected areas in south India. Issue 4 (1st May 2014) - Deepak, V.; Vasudevan, Karthikeyan
Abstract: Protected areas in developing tropical countries are under pressure from local demand for resources, and therefore it is essential to monitor rare species and prevent overexploitation of resources. The Travancore tortoise Indotestudo travancorica is endemic to the Western Ghats in southern India, where it inhabits deciduous and evergreen forests. We used multiple-season models to estimate site occupancy and detection probability for the tortoise in two protected areas, and investigated factors influencing this. During 2006–2009 we surveyed 25 trails in four forest types and estimated that the tortoise occupied 41–97% of the habitat. Tortoise presence on the trails was confirmed by sightings of 39 tortoises and 61 instances of indirect evidence of tortoises. There was considerable interannual variation in both direct and indirect evidence of tortoise presence. Although grass marshes represented only a small fraction of the protected areas, they constituted an important foraging ground for the tortoise and should be a focal point for monitoring and protection measures. Human-inhabited enclaves within the protected areas, and consequent furtive hunting, had a negative effect on occupancy by the tortoise, and therefore protected area management should include educating local communities and involving them in monitoring and protecting the species.